Issues in Feminist Film Criticism - Erens, Patricia (Indiana University Press, 1990)
Issues in Feminist Film Criticism brings together a wide variety of writings and methodologies by U.S. and British feminist film scholars. The twenty-seven essays represent some of the most influential work on Hollywood film, women's cinema, and documentary filmmaking to appear during the past decade and beyond. Among the subjects treated are images of women on the screen; questions of film realism; the notion of counter-cinema; the concept of "reading against the grain," the use of psychoanalytic theories; concerns over female spectatorship; women's place in specific genres, especially film melodrama; and issues related to the representation of lesbians and women of color. Authors represented are Lucie Arbuthnot, Linda Artel, Pam Cook, Teresa de Lauretis, Mary Ann Doane, Elizabeth Ellsworth, Lucy Fischer, Jane Gaines, Mary C. Gentile, Bette Gordon, Florence Jacobowitz, Claire Johnston, E. Ann Kaplan, Annette Kuhn, Julia Lesage, Judith Mayne, Sonya Michel, Tania Modleski, Laura Mulvey, B. Ruby Rich, Gail Seneca, Kaja Silverman, Lori Spring, Jackie Stacey, Maureen Turim, Diane Waldman, Susan Wengraf, Linda Williams, and Robin Wood.